2010
DOI: 10.1177/1944451610378131
|View full text |Cite
|
Sign up to set email alerts
|

Using Ultrasound to Identify the Central Venous Catheter Tip in the Superior Vena Cava

Abstract: In this case series of 5 patients, ultrasound was used to verify the position of the central venous catheter in the superior vena cava using the supraclavicular approach. In all patients, the position of the catheter in the superior vena cava could be verified and the results compared with a postprocedure chest X ray.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The advantage of bedside ultrasonography is the immediate availability and nonradiating imaging to identify cardiac structures, intrathoracic and intra-abdominal vasculature prior to and during placement of CVC. Killu et al 14 have described the identification of CVC artifact within the SVC as confirmation of proper CVC placement. Vezzani et al, 15 in a prospective diagnostic study, demonstrated that the sensitivity and specificity of ultrasound detection of catheter misplacement could be as high as 96% and 93%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantage of bedside ultrasonography is the immediate availability and nonradiating imaging to identify cardiac structures, intrathoracic and intra-abdominal vasculature prior to and during placement of CVC. Killu et al 14 have described the identification of CVC artifact within the SVC as confirmation of proper CVC placement. Vezzani et al, 15 in a prospective diagnostic study, demonstrated that the sensitivity and specificity of ultrasound detection of catheter misplacement could be as high as 96% and 93%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Postprocedural sonographic lung assessment for detection of occult pneumothorax and prompt placement identification has been described in the field of emergency medicine and critical care medicine. 14,15 Routinely, a chest X-ray is performed immediately after the procedure and it is possible to miss small volume pneumothorax or pneumothorax over posterior or medial locations. Ultrasound is found to be superior in diagnosing even small volume pneumothorax when compared with chest X-ray.…”
Section: Discussionmentioning
confidence: 99%
“…The hepatic vein junction to IVC and the IVC junction to right atrium are confirmatory landmarks. Reproduced with permission from Killu et al [ 26 ].…”
Section: Figurementioning
confidence: 99%
“…Evaluation of the heart and determining the EF and stroke volume can help identify the cause of hemodynamic instability and if it is cardiac in origin. Obtaining standard views of the heart is relatively easy to do and can be achieved in most patients [20]. Knowledge of image acquisition, interpretation, and the limitation to certain cardiac views taken into consideration can increase the yield of such exams.…”
Section: Introductionmentioning
confidence: 99%